2018
DOI: 10.1111/brv.12416
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐to‐mesenchymal transition in the context of epidermal growth factor receptor inhibition in non‐small‐cell lung cancer

Abstract: The identification of oncogenic driver mutations in non-small-cell lung cancer (NSCLC) has led to the development of targeted drugs. Tyrosine kinase inhibitors (TKIs) directed against the epidermal growth factor receptor (EGFR) target lung tumours bearing EGFR-activating mutations. This new therapeutic strategy has greatly improved tumour response rates. However, drug resistance invariably occurs during TKI-based treatment. Epithelial-to-mesenchymal transition (EMT) is one of the resistance mechanisms identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 113 publications
(124 reference statements)
1
26
0
Order By: Relevance
“…A remarkable proportion of cases are only detected in the advanced stage when the tumour has already metastasized to other organs, resulting in poor clinical prognosis . Epithelial‐mesenchymal transition (EMT) is generally considered to be the key progression promoting the metastasis of lung cancer . Thus, elucidating the molecular mechanism of EMT is of great significance in preventing lung cancer metastasis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable proportion of cases are only detected in the advanced stage when the tumour has already metastasized to other organs, resulting in poor clinical prognosis . Epithelial‐mesenchymal transition (EMT) is generally considered to be the key progression promoting the metastasis of lung cancer . Thus, elucidating the molecular mechanism of EMT is of great significance in preventing lung cancer metastasis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem cell (CSC) plasticity and cancer dissemination in the metastatic process were associated with EMT [10]. The phenotypic changes that characterized the transition from CSCs to differentiated cancer cells involved a process occurring in EMT [11]. It has been demonstrated that EMT was the link between benign lung diseases and lung carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that EMT was the link between benign lung diseases and lung carcinogenesis. Thus, EMT played a central role in the development of lung cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although vimentin has long been known to play a role in carcinogenesis, its potential involvement in resistance to cancer therapies has also been described, especially EGFR-directed tyrosine kinase inhibitors (TKIs) [2]. Vimentin is a type III intermediate filament protein constitutively expressed in mesenchymal cells (e.g.…”
mentioning
confidence: 99%
“…A total of 76 cases were also listed in the RMRP (56 certain, 19 probable/possible and 1 non-MM). The RMRP, established in 1993, is part of a national mesothelioma registry (ReNaM, Registro Nazionale Mesoteliomi) organized as a network of regional registries which follow the same procedures for classifying the available diagnostic evidence [2,3].…”
mentioning
confidence: 99%